PEMBINAAN PERAJIN PATUNG CETAK RESIN DI TIRTA KELAPA ART SPACE MELALUI KURSUS BAHASA INGGRIS UNTUK PEMASARAN ONLINE KHUSUSNYA MELALUI EMAIL DAN MARKETPLACE - Heribertus Binawan; Agustinus Hary Setyawan; Lu’luil Maknun (Bajang Institute, 2021)
Abstract: This PKM aims to help develop the marketing potential of resin sculpture production, which during the Covid-19 pandemic has decreased. One of these obstacles is due to the English language barrier in doing online marketing, so that the formed market tends to be limited to the local/national level. In fact, this resin molded sculpture product is likely to be of interest to the international market. Therefore, partners need assistance in the form of training in English for written communication, especially in writing emails and marketing products in the marketplace. The method used in this activity is the POACE method or Planning, Organizing, Actuating, Controlling, and Evaluating. As a result, by using English-language online marketing via email, catalogs, and market places, the sales of the statues increased and reached the international market